FAKTOR RISIKO YANG BERHUBUNGAN DENGAN PENYAKIT JANTUNG KORONER PADA USIA DEWASA MADYA (41-60 TAHUN) (Studi Kasus di RS Umum Daerah Kota Semarang) (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2015)
Coronary heart disease (CHD) is a major health problem both in developed countries and developing countries. Since there are so many factors which affect the occurrence of coronary heart disease, the efforts of prevention should be multifactorial too. The purpose of this research was to define the correlation between dislipidemia, smoking, hypertension, diabetes mellitus, obesity, physical activity level, socio-economic status, occupation, gender, dan stress level with the coronary heart disease. This research was an observational quantitative research with a case-control design was used retrospectively. This study used purposive sampling technique with the amount of each 39 people in 39 cases and in controls. Data analysis was performed using univariate and bivariate chi-square test (Î± = 0.05) and calculate the value of Odds Ratio (OR). The result showed that factors associated with coronary heart disease in middle-aged adults (41-60 years) is dyslipidemia (p = 0.0001<0,05), smoking (p = 0.0027<0,05), hypertension (p = 0.002<0,05), diabetes mellitus (p = 0.0001<0,05), obesity (p = 0.011<0,05) and stress level (p = 0.001<0,05).